Synthetic production of prenylated naringenins in yeast using promiscuous microbial prenyltransferases - Isogai, Shota; Okahashi, Nobuyuki; Asama, Ririka; Nakamura, Tomomi; Hasunuma, Tomohisa; Matsuda, Fumio; Ishii, Jun; Kondo, Akihiko (Metabolic Engineering Communications, 2021)
Reconstitution of prenylflavonoids using the flavonoid biosynthetic pathway and prenyltransferases (PTs) in microbes can be a promising attractive alternative to plant-based production or chemical synthesis. Here, we demonstrate that promiscuous microbial PTs can be a substitute for regiospecific but mostly unidentified botanical PTs. To test the prenylations of naringenin, we constructed a yeast strain capable of producing naringenin from l-phenylalanine by genomic integration of six exogenous genes encoding components of the naringenin biosynthetic pathway. Using this platform strain, various microbial PTs were tested for prenylnaringenin production. In vitro screening demonstrated that the fungal AnaPT (a member of the tryptophan dimethylallyltransferase family) specifically catalyzed C-3′ prenylation of naringenin, whereas SfN8DT-1, a botanical PT, specifically catalyzed C-8 prenylation. In vivo, the naringenin-producing strain expressing the microbial AnaPT exhibited heterologous microbial production of 3′-prenylnaringenin (3′-PN), in contrast to the previously reported in vivo production of 8-prenylnaringenin (8-PN) using the botanical SfN8DT-1. These findings provide strategies towards expanding the production of a variety of prenylated compounds, including well-known prenylnaringenins and novel prenylflavonoids. These results also suggest the opportunity for substituting botanical PTs, both known and unidentified, that display relatively strict regiospecificity of the prenyl group transfer. •Promiscuous microbial prenyltransferases replaced regiospecific botanical enzymes.•A stable yeast strain that produced naringenin from l-phenylalanine was constructed.•A fungal prenyltransferase (AnaPT) catalyzed C-3′ prenylation of naringenin.•AnaPT catalyzed the first microbial production of 3′-prenylnaringenin.•Microbial prenyltransferases permit the production of various prenylated compounds.